2014
DOI: 10.1002/ijc.29254
|View full text |Cite
|
Sign up to set email alerts
|

A high and increasing HPV prevalence in tonsillar cancers in Eastern Denmark, 2000–2010: The largest registry‐based study to date

Abstract: The aim was to explore whether the incidence of tonsillar squamous cell carcinomas (TSCCs) increased in Eastern Denmark, 2000-2010, and whether human papillomavirus (HPV) could explain the increase, and to assess the association of HPV prevalence with gender, age, and origin (i.e., the certainty of tonsillar tumor origin). We applied HPV DNA PCR and p16 immunohistochemistry to all TSCCs registered in the Danish Head and Neck Cancer Group (DAHANCA) and in the Danish Pathology Data Bank (n 5 632). Pathologists r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 50 publications
5
102
2
Order By: Relevance
“…This was most recently documented in two large Danish studies, which showed increasing proportions of HPV-positive tonsillar carcinoma and carcinomas at the base of the tongue between 2000 and 2010 (estimated annual percentage change 4.9% and 8.1%, respectively) [4,5]. If this increase in HPV prevalence has been higher among men than women and among younger than older individuals, it would support our finding of a greater decrease in mortality among male patients and younger patients with strongly HPV-associated HNSCC.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This was most recently documented in two large Danish studies, which showed increasing proportions of HPV-positive tonsillar carcinoma and carcinomas at the base of the tongue between 2000 and 2010 (estimated annual percentage change 4.9% and 8.1%, respectively) [4,5]. If this increase in HPV prevalence has been higher among men than women and among younger than older individuals, it would support our finding of a greater decrease in mortality among male patients and younger patients with strongly HPV-associated HNSCC.…”
Section: Discussionmentioning
confidence: 70%
“…The known risk factors for HNC include tobacco smoking, alcohol drinking, and certain viruses, such as the Epstein-Barr virus and human papillomavirus (HPV) [1,2]. Increase in exposure to HPV over the past few decades have been shown to influence the incidence of certain HNSCCs with significant increases of some HNSCCs, such as those of the oropharynx, especially the tonsil and base of the tongue [3][4][5]. In Denmark, an overall increase in the incidence of HNSCC has been reported, due primarily to an increased incidence of cancers at sites reported to be associated with HPV [3].…”
Section: Original Articlementioning
confidence: 99%
“…16,17 These tumors represent a distinct subgroup within head and neck squamous cell carcinoma, which are traditionally related to tobacco and alcohol abuse, and have a clearly favorable prognosis. 18,19 These differences should lead to tailored medical care in the coming years.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with HPV-positive HNC in general tend to be younger (<50 years) at time of diagnosis [24,25] and generally have a better survival and favorable prognosis compared to HPV-negative patients [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%